2023
DOI: 10.1101/2023.08.03.551900
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Learning produces a hippocampal cognitive map in the form of an orthogonalized state machine

Weinan Sun,
Johan Winnubst,
Maanasa Natrajan
et al.

Abstract: Cognitive maps confer animals with flexible intelligence by representing spatial, temporal, and abstract relationships that can be used to shape thought, planning, and behavior. Cognitive maps have been observed in the hippocampus, but their algorithmic form and the processes by which they are learned remain obscure. Here, we employed large-scale, longitudinal two-photon calcium imaging to record activity from thousands of neurons in the CA1 region of the hippocampus while mice learned to efficiently collect r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 171 publications
0
12
0
Order By: Relevance
“…One of the most surprising results in our study was that spatially tuned cells are not a guarantee of a lowdimensional neural manifold with topological correspondence to the environment. Supporting this distinction between spatial tuning and a cognitive map, experimental work has shown that, while place cells appear almost instantaneously in novel environments 84 , a cognitive map only emerges after multiple days of exposure 26,28 and relies on weakly tuned cells 28,50 . In addition to predicting sequences of sensory inputs, our results suggest that a head direction signal is critical to learn a cognitive map from viewpoint-dependent observations.…”
Section: Discussionmentioning
confidence: 98%
“…One of the most surprising results in our study was that spatially tuned cells are not a guarantee of a lowdimensional neural manifold with topological correspondence to the environment. Supporting this distinction between spatial tuning and a cognitive map, experimental work has shown that, while place cells appear almost instantaneously in novel environments 84 , a cognitive map only emerges after multiple days of exposure 26,28 and relies on weakly tuned cells 28,50 . In addition to predicting sequences of sensory inputs, our results suggest that a head direction signal is critical to learn a cognitive map from viewpoint-dependent observations.…”
Section: Discussionmentioning
confidence: 98%
“…The significance of reward-relative sequences in the brain may lie in their connection to hidden state estimation 7,43,[161][162][163][164][165] , a concept closely related to generalization 28,166 . Hidden state estimation refers to the process by which an animal or agent infers an unobservable state, such as the probability of receiving a reward under a certain set of conditions, in order to choose an optimal behavioral strategy 161 .…”
Section: Discussionmentioning
confidence: 99%
“…Because leaf1 and leaf2 neural representations were similar in naive mice (Figure 2j), we hypothesized that the fine behavioral discrimination between leaf1 and leaf2 stimuli requires orthogonalization of their neural representations [27, 34]. We tested this by comparing the projections of leaf2 onto the leaf1-circle1 coding direction (Figure 3f,g).…”
Section: Novelty Responses and Neural Orthogonalizationmentioning
confidence: 99%
“…In the mouse visual cortex, anticipatory responses to learned stimulus sequences have been interpreted as evidence for predictive coding, which is a form of unsupervised learning [22, 23]. Neural plasticity in the hippocampus has sometimes been interpreted as sensory compression [24, 25], which is also a type of unsupervised learning, though it has typically been linked to spatial rather than sensory representations [26, 27]. It is thus still not known how widely unsupervised learning may affect sensory neural representations.…”
mentioning
confidence: 99%